Fondamentaux hygiénistes ou résilience environnementale ? La gestion des déchets en crise Covid - Hélène Beraud; Mathieu Durand; Rebecca Oates; Frédéric Gbedande (Développement Durable et Territoires)
Since the end of the 19th century, urban management priorities have evolved from hygienic imperatives to more environmentalist logics (Barraqué, 2014). The global spread of the pandemic in 2020 and the sudden implementation of initially strict containment measures have led waste management stakeholders to review their overall strategy. The objective of this article is to understand how waste management services, which are socially not very visible, but nevertheless essential, have been reorganised by the stakeholders since March 2020. The aim is to put these adaptations into perspective with regard to the various waste management issues, in particular by comparing health and environmental considerations.